2016
DOI: 10.1084/jem.20151932
|View full text |Cite
|
Sign up to set email alerts
|

E3 ubiquitin ligase Cbl-b negatively regulates C-type lectin receptor–mediated antifungal innate immunity

Abstract: Innate immune responses mediated by C-type lectin receptors Dectin-2 and Dectin-3 against fungal infections are negatively regulated by Cbl-b ubiquitination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 53 publications
0
62
1
Order By: Relevance
“…As these CLRs lack a signaling domain, heterodimeric complexes signal via the ITAM-coupled adaptor FcRγ (9). Following fungal recognition, the E3 ubiquitin ligase CBLB ubiquitinates dectin-1, dectin-2, and SYK, targeting them for degradation (50)(51)(52). In systemic candidiasis, Cblb -/-mice exhibit reduced renal fungal burden and improved survival due to decreased inflammation-driven tissue damage (50)(51)(52).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As these CLRs lack a signaling domain, heterodimeric complexes signal via the ITAM-coupled adaptor FcRγ (9). Following fungal recognition, the E3 ubiquitin ligase CBLB ubiquitinates dectin-1, dectin-2, and SYK, targeting them for degradation (50)(51)(52). In systemic candidiasis, Cblb -/-mice exhibit reduced renal fungal burden and improved survival due to decreased inflammation-driven tissue damage (50)(51)(52).…”
Section: Introductionmentioning
confidence: 99%
“…Following fungal recognition, the E3 ubiquitin ligase CBLB ubiquitinates dectin-1, dectin-2, and SYK, targeting them for degradation (50)(51)(52). In systemic candidiasis, Cblb -/-mice exhibit reduced renal fungal burden and improved survival due to decreased inflammation-driven tissue damage (50)(51)(52). In contrast, TRIM62-mediated CARD9 ubiquitination is essential for BCL10 interactions, NF-κB activation, and defense against candidiasis (53).…”
Section: Introductionmentioning
confidence: 99%
“…Cbl-mediated polyubiquitination leads to protein degradation via the lysosome and proteasome (56). Cbl-family ligases must in turn be tightly regulated to prevent hyperresponsive or aberrant signaling while maintaining proper pathogen clearance (57). Although highly homologous, c-Cbl and Cbl-b target different subsets of signaling proteins for degradation (58, 59), with c-Cbl targeting the SFKs, including Lyn (60, 61), and Cbl-b interacting with ITAM-coupled receptors and other kinases (31, 53, 57).…”
Section: Discussionmentioning
confidence: 99%
“…Cbl-family ligases must in turn be tightly regulated to prevent hyperresponsive or aberrant signaling while maintaining proper pathogen clearance (57). Although highly homologous, c-Cbl and Cbl-b target different subsets of signaling proteins for degradation (58, 59), with c-Cbl targeting the SFKs, including Lyn (60, 61), and Cbl-b interacting with ITAM-coupled receptors and other kinases (31, 53, 57). c-Cbl is thought to interact with active SFKs through the SFK activation-loop phosphotyrosine residue, which binds the c-Cbl PTB domain (62), and through the SFK SH3 domain, which binds the c-Cbl PXXP motifs (63).…”
Section: Discussionmentioning
confidence: 99%
“…1). Recently, 3 complementary studies showed that the E3 ubiquitin ligase CBLB targets dectin-1, dectin-2, macrophage C-type lectin (MCL) (described in more detail below), and their adaptor molecule Syk for degradation, and thus exerts a strong anti-inflammatory effect [7-9]. The authors showed that treatment strategies involving the inhibition of CBLB led to increased inflammatory responses and improved the outcome of experimental candidiasis, which provides evidence that CBLB might represent a therapeutic target in fungal disease.…”
Section: Dectin-1mentioning
confidence: 99%